Spatial characterization of edge zonal flows in the TJ-II stellarator: the roles of plasma heating and isotope mass. (4th March 2021) - Losada, U; Kobayashi, T; Ohshima, S; Cappa, A; Van Milligen, B; Liniers, M; López-Miranda, B; Liu, B; Pastor, I; Silva, C; Hidalgo, C
Abstract: In this article, we report the latest results for the impacts of the isotope mass and the plasma heating scenario on the spatiotemporal characteristics of the low-frequency zonal flow (ZF)-like electrostatic oscillation found in the plasma edge of the TJ-II stellarator. The radial profile of the toroidal cross-coherence in low-frequency floating potential fluctuations (1 < f < 25 kHz), known as long-range correlations (LRCs), was explored along the plasma boundary region by a dual Langmuir probe system. The study was performed using electron cyclotron resonance heating (ECRH)- and neutral beam injection (NBI)-heated plasmas with two different isotope concentrations: pure hydrogen plasmas and plasmas dominated by deuterium ( ≈ 70 % D ). The highest toroidal coherence levels are detected for floating potential oscillations at less than 10 kHz in hydrogen and deuterium plasmas, in both the ECRH and NBI heating schemes. The radial extent of the LRC profile is clearly larger in the ECRH than in the NBI-heated plasma scenarios. While the maximum amplitude of the LRC does not show a significant dependence on isotope mass, the relation between the LRCs' radial sizes in plasmas and different isotope masses increases with the isotope mass in NBI-heated scenarios. These results provide the first experimental observation of ZFs with a larger radial size in deuterium than in hydrogen plasmas.